Meniscus tear developed by pulling of the anomalous insertion of medial meniscus on anterior cruciate ligament - Wang, Joon Ho (Springer-Verlag, 2011)
There is no report regarding a medial meniscus tear arising from an anomalous insertion of medial meniscus on the ACL, which seemed to be developed by the same mechanism as ACL tear. A case of a combined medial meniscus tear with ACL tear in the presence of an anomalous insertion of the medial meniscus on the ACL is reported.